2008
DOI: 10.1002/glia.20701
|View full text |Cite
|
Sign up to set email alerts
|

The four‐and‐a‐half‐LIM protein 2 (FHL2) is overexpressed in gliomas and associated with oncogenic activities

Abstract: Four-and-a-half-LIM protein 2 (FHL2) is a member of FHL protein family, which plays a crucial role in regulating gene expression, cell survival, and migration. Although its function in oncogenesis appears to be tumor type-specific, its roles in glioma formation and development are yet to be elucidated. In the present study, we demonstrated that the mRNA level of FHL2 was elevated in both low- and high-grade glioma samples. Overexpression of FHL2 stimulated the proliferation, anchorage-independent growth, and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 34 publications
(39 reference statements)
3
24
0
Order By: Relevance
“…An altered FHL2 expression was observed in osteosarcoma cells treated with plumbagin, similarly to the results reported in previous studies (35,39). In addition, previous studies have demonstrated that FHL2 gene expression in human soft tissue cancers is variable depending on the cell type; FHL2 was revealed to be overexpressed in breast cancer (40), glioma (41), lung cancer (42), colon carcinoma (20) and gastrointestinal cancer (43) cells compared with cells from normal tissue.…”
Section: Discussionsupporting
confidence: 88%
“…An altered FHL2 expression was observed in osteosarcoma cells treated with plumbagin, similarly to the results reported in previous studies (35,39). In addition, previous studies have demonstrated that FHL2 gene expression in human soft tissue cancers is variable depending on the cell type; FHL2 was revealed to be overexpressed in breast cancer (40), glioma (41), lung cancer (42), colon carcinoma (20) and gastrointestinal cancer (43) cells compared with cells from normal tissue.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, these A549 Ú -cells, whilst able to grow in mouse xenografts, required longer induction periods with smaller tumours than their Ú + parents. This suggests a clear difference in phenotype, perhaps due to differences in nuclear gene expression (96)(97)(98). Similar results have been noted in breast cancer cells (99).…”
Section: Creation Of Mtdna-less Cells (ú -) Cavalli Et Alsupporting
confidence: 80%
“…Previous studies have shown that FHL2 may act as both an oncoprotein or a tumor suppressor depending on the type of cancer (13)(14)(15)(16)(17)(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…FHL2 was first identified in human rhabdomyosarcoma cells as a downregulated gene indicating a role as tumor suppressor (13) and reduced FHL2 expression was also found in prostate and hepatocellular cancer (14,15). In contrast, increased expression of FHL2 was detected in breast, lung, and ovarian cancer, as well as glioblastoma and melanoma (16)(17)(18)(19)(20). Further, Wang et al found higher FHL2 expression in colon cancerous tissues compared to normal tissues, and the same authors described, that suppression of FHL2 in a colon cancer cell line with endogenously high FHL2 expression inhibited tumor growth (21).…”
Section: Introductionmentioning
confidence: 99%